How Does Transcranial Magnetic Stimulation Influence Glial Cells in the Central Nervous System? - Cullen, Carlie L.; Young, Kaylene M. (Frontiers in Neural Circuits, 2016)
Transcranial magnetic stimulation (TMS) is widely used in the clinic, and while it has a direct effect on neuronal excitability, the beneficial effects experienced by patients are likely to include the indirect activation of other cell types. Research conducted over the past two decades has made it increasingly clear that a population of non-neuronal cells, collectively known as glia, respond to and facilitate neuronal signalling. Each glial cell type has the ability to respond to electrical activity directly or indirectly, making them likely cellular effectors of TMS. TMS has been shown to enhance adult neural stem and progenitor cell proliferation, but the effect on cell survival and differentiation is less certain. Furthermore there is limited information regarding the response of astrocytes and microglia to TMS, and a complete paucity of data relating to the response of oligodendrocyte-lineage cells to this treatment. However, due to the critical and yet multifaceted role of glial cells in the CNS, the influence that TMS has on glial cells is certainly an area that warrants careful examination.